Inspection of additively manufactured components by spatially resolved acoustic spectroscopy - Dryburgh, Paul (2022)
This thesis presents the development of spatially resolved acoustic spectroscopy (SRAS) for the materials characterisation of new alloys and additive manufacturing specimens. SRAS is an acoustic microscopy technique that uses laser-generated and detected ultrasound to probe the material properties of crystalline specimens. Laser generation allows the surface acoustic wave velocity to be measured across the specimen and is a valuable tool for highlighting the grain structure. In anisotropic materials, inversion of the SAW velocity in multiple directions is used to determine the crystalline orientation.